Go frutti: the importance of fruits consumption through motion graphic / Mohd Firdaus As-Saufi Pahmi - Pahmi, Mohd Firdaus As-Saufi (Faculty of Art and Design, 2020)
Go Frutti: to educate Malaysia about the importance of fruits consumption through Motion Graphic.